Effect of Substrate Concentration on Hydrogen Production Rate in Microbial Electrolysis Cell using Mathematical Modelling based on Simplified Biofilm Growth - Mohamad Afiq, Mohd Asrul; Mohd Farid, Atan; Hafizah, Abdul Halim Yun; Josephine Lai, Chang Hui (2024)
The non-linearity of the interactions between reaction and kinetics at the level of microbial biofilm growth leads to dynamic effects of biohydrogen production in the microbial electrolysis cell (MEC). A sensitivity analysis using the simplified MEC model investigates the influence of the hydrogen production profile with the variation of the initial substrate concentration in the influent. The aim of the model simulation is to evaluate the sensitivity of the initial substrate concentration in the feed to the hydrogen production rate at maximum steady state. The ode45 solver computes the code of the mathematical model using MATLAB. The preliminary results show that the substrate concentration profile has the opposite effects for acetate. The results also prove that a double chamber MEC resists methane formation due to the dominant concentration profile of electroactive bacteria that counteract both acetoclastic methanogenic bacteria and hydrogenotrophic methanogenic bacteria. The sensitivity test of the model shows that the hydrogen production rate increases rapidly when the initial concentration of the substrate in the influent decreases and simultaneously contributes to the fluctuation effect of the non-linear curve. The hydrogen production rate increases up to the maximum steady state of 0.033 L‧day-1, while the decrease in substrate concentration reaches its steady state at a minimum of 476 mg‧L-1. The modelling study also has the potential for future extension by implementing a novel framework as a strategy to address the dynamic behaviour of hydrogen production rate in the MEC over multiple retention days.